IN-VIVO ANTI-INFLAMMATORY ACTIVITIES OF ETHANOLIC ROOT EXTRACT OF BAUHINIA VARIEGATA LINN - PRABHA, P.MEENA; KAMALAKKANNAN, V.; Kumaran, K.S.G.arul; SAMBATHKUMAR, R. (International Journal of Pharmacy and Pharmaceutical Sciences, 2014)
Objective: The objective of present study was to evaluate the anti-inflammatory activity of ethanolic extract of Bauhinia variegate root. Methods: In the present study BVEE at 200 and 400 mg/kg body weight was studied for anti-inflammatory activities in different animal models.. Anti- inflammatory activity was carried out by using carrageenan induced paw edema model and cotton pellet induced granuloma model in wistar rats. Results: The results shows that BVEE possess anti-inflammatory activity in acute as well as sub acute models of inflammation in rats. BVEE (200 and 400 mg/kg) showed significant (p <0.01) anti-inflammatory activity by reducing the paw edema volume in carrageenan-induced paw edema in rats in the late phase (2to4h)regulated by prostaglandins and leucotrienes and in cotton pellet induced granuloma model BVEE decreased dry weight of granuloma. Conclusion: The observed pharmacological activity may be due to presence of phytochemical compounds present in the extract like alkaloids, flavonoids, phenols, saponins and tannins.